TITLE: THE INFLUENCE OF MENTAL ACCOUNTING AND RISK AVERSION ON INVESTMENT DECISIONS (SURVEY ON ONLINE GAME PLAYERS) - Behruzbek Oroqulov; Rozmita Dewi Yuniarti Rozali; Elis Mediawati; Mekhrangiz Khudayarova (Journal of Management and Innovation Entrepreneurship (JMIE), 2026)
This study investigates how mental accounting and risk aversion shape investment decisions among online game players in Indonesia. Drawing on Thaler's (1985, 1999) mental accounting framework and Kahneman and Tversky's (1979) Prospect Theory, the research explores whether the behavioral biases commonly found in traditional investor populations also emerge within digitally mediated economic contexts. A quantitative approach was used, with primary data collected through a structured online questionnaire administered to 122 active online game players. All variables were measured using a five-point Likert scale, and the data were analyzed through multiple linear regression using SPSS version 26. The results confirm that both mental accounting and risk aversion significantly and positively influence investment decisions. Together, these two variables explain a meaningful portion of the variance in investment behavior, with the overall model reaching statistical significance. These findings indicate that behavioral finance mechanisms remain relevant within virtual economic environments, and carry practical implications for financial educators and investment platform designers working with digitally engaged young investors.